Knowledge and attitudes of thalassaemia among high-risk indigenous university students in Bangladesh: A pilot study. - Md Mahbub Hasan; Khaza Md Kapil Uddin; Syed Mohammad Lokman; Kallyan Chakma; Aung Chaing-U Pulu; Adnan Mannan; Enayetur Raheem; Shahed Ahmad Chowdhury; Mohammad Sorowar Hossain (PLoS ONE, 2023)
Background and objectives Thalassaemia is an inherited life-threatening but preventable haemoglobin disorder. South Asian countries, including Bangladesh, are the hotspots of the world's thalassaemia belt. Indigenous communities are underprivileged and vulnerable to genetic disorders, including thalassaemia. Understanding the perspectives of thalassaemia of future community leaders (indigenous university students) is critical for developing a tailor-made preventive strategy relevant to their communities. In this study, we aimed to assess the level of knowledge and attitudes towards thalassaemia among indigenous university students and determine their thalassaemia carrier status. Methods A cross-sectional survey was conducted among 251 tribal university students using a published questionnaire between May and October 2018. The main survey instrument consisted of 22 anonymous questions. Descriptive and inferential statistical procedures were used for data analysis. Results More than half (55%) of the indigenous students had never heard the term 'thalassaemia'. Around half (49%) of the marriages in their communities were consanguineous. The mean knowledge score was abysmal (4.91±2.65 out of a 12-point scale), which was not associated with the consanguinity of their parent but home districts. Multiple linear regression of demographic variables on the total knowledge score revealed that the overall knowledge is significantly associated with their home district (p< 0.05). Participants from science disciplines scored more than 1 point than their counterparts from Arts and Humanities (p = 0.08615). Conclusions For the first time, this study has identified knowledge gaps and misperceptions about thalassaemia among university students from indigenous communities in the southeastern region of Bangladesh. This study serves as a baseline for future interventions (premarital and prenatal screening) targeting future community leaders.